OPINI PUBLIK INTENAL MENGENAI GAYA KOMUNIKASI KEPEMIMPINAN WALIKOTA (Studi Terhadap Gaya Komunikasi Kepemimpinan Eddy Rumpoko Walikota Batu) - Imam Patkurroji; Kiki Hilda Lestari (Universitas Merdeka Malang, 2017)
AbstractSeen from the internal public opinion: how do these communications Eddy, the internal public in their daily activities, the effectiveness of communication between the high officials, and how public opinion has been on the leadership style of communication Eddy Rumpoko. In this case, public opinion is presented as feedback from public officials as an internal, the communication style of leadership adopted by Eddy Rumpoko. As a simple guy, did not appear and also close to the people, how public opinion is formed, officials, during work time to accompany Eddy in Batu city government offices. Data collection techniques through the process of observation, interviews and using data documentation and publications to support data collection and analysis process. The analysis is done by emphasizing subjective and field findings. The results of this study is the leadership style of combining a top down and bottom up into a mainstay of Edy Rumpoko. The main strategy of leadership is motivation.Keywords: Communication, Leadership Style , Public OpinionDOI : https://doi.org/10.26905/nomosleca.v3i1.1486